2010
DOI: 10.1038/cgt.2010.19
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Efp by DNA-modified small interfering RNA inhibits breast cancer cell proliferation and in vivo tumor growth

Abstract: The estrogen-responsive gene Efp promotes the growth of breast cancer cells by stimulating the degradation of a negative cell-cycle regulator, 14-3-3s, and is hence considered a suitable molecular target for breast cancer therapy. The use of small interfering RNA (siRNA) and its derivatives to silence cancer-related genes is being investigated with the aim of identifying clinical applications for these molecules. Recently, it has been shown that DNA-modified siRNA (chimeric siRNA) has good potential in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…In the present in vivo tumor growth analysis, we used siRNA/DNA, since it has been reported that siRNA/DNA can overcome the disadvantages of usual siRNAs such as the problems of instability [48], induction of silencing of unintended genes (off-target effects) [49], or induction of immune response in vivo [50]. On the other hand, it has previously been reported that gene silencing induced by siRNA/DNA is likely to be less effective than that induced by its unmodified counterparts, because siRNA/DNA exhibits weaker activity for formation of am RNA-induced silencing complex [13,51]. Considering these facts, we adopted a multiple siRNA/ DNA injection protocol (in the present study, thrice, at days 0, 7, and 14) as described elsewhere [51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present in vivo tumor growth analysis, we used siRNA/DNA, since it has been reported that siRNA/DNA can overcome the disadvantages of usual siRNAs such as the problems of instability [48], induction of silencing of unintended genes (off-target effects) [49], or induction of immune response in vivo [50]. On the other hand, it has previously been reported that gene silencing induced by siRNA/DNA is likely to be less effective than that induced by its unmodified counterparts, because siRNA/DNA exhibits weaker activity for formation of am RNA-induced silencing complex [13,51]. Considering these facts, we adopted a multiple siRNA/ DNA injection protocol (in the present study, thrice, at days 0, 7, and 14) as described elsewhere [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has previously been reported that gene silencing induced by siRNA/DNA is likely to be less effective than that induced by its unmodified counterparts, because siRNA/DNA exhibits weaker activity for formation of am RNA-induced silencing complex [13,51]. Considering these facts, we adopted a multiple siRNA/ DNA injection protocol (in the present study, thrice, at days 0, 7, and 14) as described elsewhere [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…9 More recently expression of TRIM25 has also been associated with ovarian and breast cancer and is thought to positively promote cell growth by targeting the cell cycle regulator 14-3-3 sigma for proteasomal degradation. [10][11][12] Therefore, TRIM25 may act as a tumor promoter, but whether TRIM25 has a function in lung cancer development remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…EFP is a well-established downstream target gene of estrogen-ERα signaling [18, 29]. The expression of EFP mRNA and protein can be efficiently induced in response to estrogen treatment in human breast cancer cells and positively associated with ERα expression status in human primary breast cancer tumors [17, 20].…”
Section: Discussionmentioning
confidence: 99%